A subnational analysis of China's activism in regional cooperation along the borders - Li, Xirui (Nanyang Technological University, 2023)
Subnational governments at international land borders are at an advantage to participate in regional cooperation, due to geographical convenience. However, although such subnational governments belonging to the same country may have been empowered and encouraged by their respective national governments to engage in regional cooperation, their levels of activism vary. Some subnational governments view promoting regional cooperation as their guiding development philosophy and invest resources into nearly every aspect of such cooperation, whereas others view it as merely one of their development strategies and spare efforts or resources in only a few select aspects. First, in contrast to previous research that relies on a single indicator for comparison, I propose a composite index in this dissertation to comprehensively compare the participation of subnational governments in regional cooperation. Second, based on local liberalism and the role of subnational governments’ perceptions in their decision-making, I develop a new analytical framework, Embedded Local Liberalism, to explain the variation among subnational governments. It argues that economic benefits from globalization motivate subnational governments to engage in regional cooperation, but that this economic motivation is moderated by subnational governments’ perceptions of the geopolitical environment where their state is situated in the region. This overcomes the limitation of previous research that overemphasized domestic political factors while ignoring international political factors. To apply the framework, I compare and analyze the activism of three Chinese provincial governments with inland international borders in regional cooperation from 2004 to 2019. This dissertation thus contributes to a previously under-explored subnational perspective of China's increasing activism in regional and international engagement. The findings indicate that the engagement of subnational governments in regional/international cooperation and regional/world order are mutually reinforcing; subnational governments’ participation can strengthen the existing order, but the extent to which they are willing to participate is also contingent on the existing order. In addition, my research suggests that decentralization and support from the national government may not be sufficient to mobilize subnational governments to conduct regional and international cooperation. Before subnational governments become willing and able to play a larger role in regional and international cooperation, the state and its cooperative partners must first shape subnational governments’ positive perceptions of their state’s geopolitical environment by establishing robust and resilient bilateral and multilateral relationships.